The Sage handbook of qualitative research - Denzin, Norman K.; Lincoln, Yvonna S. (Thousand Oaks, California Sage Publications, Inc., 2018)
"The substantially updated and revised Fifth Edition of this landmark handbook presents the state-of-the-art theory and practice of qualitative inquiry. Representing top scholars from around the world, the editors and contributors continue the tradition of synthesizing existing literature, defining the present, and shaping the future of qualitative research. The Fifth Edition contains 19 new chapters, with 16 revised making it virtually a new volume while retaining six classic chapters from previous editions. New contributors to this edition include Jamel K. Donnor and Gloria Ladson-Billings; Margaret Kovach; Paula Saukko; Bryant Keith Alexander; Thomas A. Schwandt and Emily F. Gates; Johnny Saldaña; Uwe Flick; Mirka Koro-Ljungberg, Maggie MacLure, and Jasmine Ulmer; Maria Elena Torre, Brett G. Stoudt, Einat Manoff, and Michelle Fine; Jack Bratich; Svend Brinkmann; Eric Margolis and Renu Zunjarwad; Annette N. Markham; Alecia Y. Jackson and Lisa A. Mazzei; Jonathan Wyatt, Ken Gale, Susanne Gannon, and Bronwyn Davies; Janice Morse; Peter Dahler-Larsen; Mark Spooner; and David A. Westbrook"--Publisher.
The discipline and practice of qualitative research / Norman K. Denzin and Yvonna S. Lincoln -- Part 1. Locating the field. A history of qualitative inquiry in social and educational research / Frederick Erickson -- Ethics and politics in qualitative research / Clifford G. Christians -- Ethics, research regulations, and critical social science / Gaile S. Cannella and Yvonna S. Lincoln -- Part 2. Paradigms and perspectives in contention. Paradigmatic controversies, contradictions, and emerging confluences, revisited / Yvonna S. Lincoln, Susan A. Lynham, and Egon G. Guba -- Feminist qualitative research in the millenium's first decade: developments, challenges, prospects / Virginia Olesen -- Feminist qualitative research: emerging lines of inquiry / Marjorie L. DeVault -- Critical race theory and the postracial imaginary / Jamel K. Donnor and Gloria Ladson-Billings -- Doing Indigenous methodologies: a letter to a research class / Margaret Kovach -- Critical pedagogy and qualitative research: advancing the bricolage / Joe L. Kincheloe, Peter McLaren, Shirley R. Steinberg, and Lilia D. Monzó -- Methodologies for cultural and social studies in an age of new technologies / Paula Saukko -- Queer/quare theory: worldmaking and methodologies / Bryant Keith Alexander -- Part 3. Strategies of inquiry. The marketization of research: implications for qualitative inquiry / Julianne Cheek -- Case study methodology / Thomas A. Schwandt and Emily F. Gates -- Performance ethnography / Judith Hamera -- Ethnodrama and ethnotheatre: research as performance / Johnny Saldaña -- Advancing a constructionist analytics / James A. Holstein -- Evolving grounded theory and social justice inquiry / Kathy Charmaz, Robert Thornberg, and Elaine Keane -- Triangulation / Uwe Flick -- D...a...t...a..., data++, data, and some problematics / Mirka Koro-Ljungberg, Maggie MacLure, and Jasmine Ulmer -- In the name of human rights: I say (how) you (should) speak (before I listen) / Antjie Krog -- Critical participatory action research on state violence: bearing wit(h)ness across fault lines of power, privilege, and dispossession / María Elena Torre, Brett G. Stoudt, Einat Manoff, and Michelle Fine -- Part 4. Methods of collecting and analyzing empirical materials. Observation in a surveilled world / Jack Bratich -- Narrative inquiry: toward theoretical and methodological maturity / Susan E. Chase -- Critical arts-based inquiry: performances of resistance politics / Susan Finley -- The interview / Svend Brinkmann -- Visual research / Eric Margolis and Renu Zunjarwad -- Autoethnography and the other: performative embodiment and a bid for utopia / Tami Spry -- Ethnography in the digital internet era: from fields to flows, descriptions to interventions / Annette N. Markham -- Analyzing talk and text / Anssi Peräkylä and Johanna Ruusuvuori -- Focus group research and/in figured worlds / George Kamberelis, Greg Dimitriadis, and Alyson Welker -- Thinking with theory: a new analytic for qualitative inquiry / Alecia Y. Jackson and Lisa A. Mazzei -- Creating a space in between: collaborative inquiries / Jonathan Wyatt, Ken Gale, Susanne Gannon, and Bronwyn Davies (JKSB) -- Part 5. The art and practices of interpretation, evaluation, and representation. Evidence, criteria, policy, and politics: the debate about quality and utility in educational and social research / Harry Torrance --Reframing rigor in qualitative inquiry / Janice Morse -- Writing: a method of inquiry / Laurel Richardson and Elizabeth Adams St. Pierre -- The elephant in the living room, or extending the conversation about the politics of evidence / Norman K. Denzin -- Braiding narrative ethnography with memoir and creative nonfiction / Barbara Tedlock -- Qualitative evaluation: methods, ethics, and politics with stakeholders / Peter Dahler-Larsen -- Part 6. The future of qualitative research. Qualitative research and global audit culture: the politics of productivity, accountabilty and possibility / Marc Spooner -- Critical issues for qualitative research / David A. Westbrook.
Revised edition of: Handbook of qualitative research. 2nd edition. ©2000.
Includes bibliographical references and indexes.
Keywords: Social sciences -- Research; Qualitative research